Teachers' engagement with learners in inclusive foundation phase classrooms: a case study analysis - Skae, Vera Astrid (Rhodes University, Faculty of Education, Department of Education, 2019)
Since 2001, South African teachers have been attempting to practise inclusive education in classrooms in ordinary, public schools. Previous research has shown the many challenges South African teachers face in our current educational environment. Strong arguments, however, have been made for more research to be done on actual teacher engagement with learners in our ordinary, public school classrooms, and the extent to which classroom practices are inclusive (Engelbrecht, Nel, Nel & Tlale, 2015, p. 3). This study sought to do an in-depth critical analysis of three foundation phase teachers and their engagement with learners in their classrooms at an Eastern Cape school. The aim was to examine how inclusive education was being enacted by the teacher with learners in real classroom settings, with particular attention paid to ways in which learners experience barriers to learning. A micro-level analysis was conducted in a single unit case study and using a qualitative research approach in an interpretive paradigm. Questionnaires, observations, and semi-structured interviews were conducted in an attempt to gather in-depth data. It was heartening to observe the extent to which inclusive education and practices were being enacted at the school and in the classrooms, and instructive in providing examples of what can work in the South African context. Key findings of this study include the generation of a framework for analysing inclusive classroom practice at the micro level. Criteria were identified as indicators of inclusive education of learners including those experiencing barriers to learning in the classroom. This study builds on and extends what has been developed at the macro and micro level of inclusive education in schools and in the classroom. It found that a number of challenges remain for enabling the implementation of an inclusive education. At the macro level, these include the provision of clear directives for implementation of inclusive education by the appropriate authorities; the provision of well-structured professional teacher training and development programmes in inclusive classroom practices, as well as in barriers to learning and how to address them; and the provision of funding for school and classroom infrastructure and resources. At the micro level, these include the successful implementation by teachers of inclusive classroom practices and the provision of the necessary support for learners experiencing barriers to learning in their classrooms, including expert personnel, resources, and assistive devices.
Keywords: Early childhood education -- South Africa -- Eastern Cape -- Case studies; Education and state -- South Africa